2018
DOI: 10.5964/ejop.v14i3.1563
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of perceived social support in the relationships between general causality orientations and locus of control with psychopathological symptoms

Abstract: The main aim of this study is to investigate the mediator role of perceived social support in the relationship between general causality orientations and locus of control with psychopathological symptoms. Total 751 participants were consisted of 558 female ages between 17 and 36 (Female M = 19.03, SD = 0.09) (74.3%), 192 male ages between 17 and 37 (Male M = 20.71, SD = 0.17) (25.6%) and a participant who did not provide any gender information. We used the General Causality Orientations Scale (GCOS) and Locus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 54 publications
(67 reference statements)
0
9
0
1
Order By: Relevance
“…When evaluated the findings of the first study (Dağ & Şen, 2018) and the findings that are obtained here, it could be concluded that general causality orientations is an important variable in the relationship between attachment and psychopathology. In summary, it can be said that the general causality orientation variable plays a remarkable role in the relationship between attachment and psychopathology for future studies.…”
Section: Limitations and Future Directionsmentioning
confidence: 77%
“…When evaluated the findings of the first study (Dağ & Şen, 2018) and the findings that are obtained here, it could be concluded that general causality orientations is an important variable in the relationship between attachment and psychopathology. In summary, it can be said that the general causality orientation variable plays a remarkable role in the relationship between attachment and psychopathology for future studies.…”
Section: Limitations and Future Directionsmentioning
confidence: 77%
“…Türkiye"de Kendini Belirleme Kuramı (Deci ve Ryan, 1985a) temel alınarak nedensellik yönelimini değerlendirmek üzere geliştirilen ölçeğin uyarlama, geçerlik ve güvenirlik çalışması oldukça yenidir ve yapılan çalışmalar da sınırlıdır (bknz. Bıçaksız vd., 2019;Dağ ve Şen, 2018;Şen ve Dağ, 2020). Benzer şekilde bağlanma stilleri ile Kendini Belirleme Kuramı"nda (Deci ve Ryan, 1985a) belirtilen psikolojik ihtiyaçlar ile nedensellik yönelimleri arasındaki ilişkiyi çalışan araştırmalar da sınırlıdır.…”
Section: Discussionunclassified
“…Furthermore, their study found an interaction effect between perceived social support and negative life events in a clinical group (Miloseva et al, 2017) and depression is one of the reasons for causing postpartum depression during pregnancy (Norhayati et al, 2015). Perceived social support is found to be a moderator in the relationship between general awareness of psychological symptoms (i.e., OCD symptomology, general psychological symptoms, and Depressive symptoms) and the locus of control (Dağ & Şen, 2018;Bukhari & Afzal, 2017). However, another study determined a novel contribution of psychosocial and biological bodies to explore how neuroticism, perceived social support from the father, and cortisol reactivity contribute to increasing the level of depression during pregnancy (Kofman et al, 2019).…”
Section: Of 13mentioning
confidence: 99%